A Study on Appraisal of Post Operative Complications Among Abdominal Surgeries Using Clavien –Dindo Classification - Manekk, Roshani S; Akther, Jawed (International Journal of Psychosocial Rehabilitation, 2020)
Background: Clavien and Dindo initially gave a classification for postoperative complications which was revised and was made valid at a later date. The Clavien-Dindo classification version is modified from the initial classification of complications which was published in 1992. The basis of selecting this topic was firstly to re-evaluate the applicability of this classification in defining and grading the post-operative complications after abdominal surgeries and Secondly to re-introduce the concept of recording the post operative complications, in a standarized manner.Objectives: To classify postoperative complications among abdominal surgeries using clavein-dindo classification. To correlate pre-operative risk factors & co-morbid factors with complications, classified as per clavien-dindo classification. To correlate abdominal surgeries with complications, classified as per clavien-dindo classification. Methodology: Routine investigation will be done in all cases along with specific investigations if any, depending upon the provisional diagnosis and their requirement. The complexity of surgery will be assessed according to a modified classification for complexity of surgeries. Post-operative complications and management will be recorded, and then postsurgical complication will be classified based on clavien-dindo classification and assessed. Among the above cases those developing complications will be randomly selected to make total participant size of 100. Results: In this Study we expect to derive that the patient’s with high preoperative HbA1c levels i.e >6.0 percent is having a higher risk to develop postoperative complications. We also expect that patient’s with preoperative BMI of ≥ 30kg/m2 and BMI ≥ 35kg/m2 have increased postoperative morbidity. We also expect that Clavein-Dindo classification is an easy tool to evaluate the post operative complications after Abdominal surgeries in an Indian setting. Conclusion: After the completion of this study we expect to conclude that measurement of HbA1c preoperatively can identify patients at high risk of post-operative complications. We also hope to conclude that obesity can lead to adverse post operative complications especially respiratory and wound complications and that Clavein-Dindo classification can be used as a standard classification to evaluate such post operative complications after Abdominal surgeries in an Indian setting.